Yapı Malzemesi Üretiminde Kullanılan Bor Türevlerine Yönelik Çalışmaların Analizi - Samuk, Tufan Bora (Fen Bilimleri Enstitüsü, 2015)
Birlikte kullanıldığı malzemeye oldukça önemli nitelikler kazandıran ve bu nedenle de gün geçtikçe dünyadaki kullanımı hızla artan bor ve türevlerinin yapı malzemesindeki kullanım alanlarını irdelemek amacıyla yapılan bu çalışmada öncelikle bor tanıtılmış, borun tarihçesi hakkında bilgi verilmiş, bor mineralleri ve kullanım alanları anlatılmıştır. Kullanım alanlarının öncelikle niteliği, sonra niceliği ön planda tutularak; cam sanayisinde, seramik sanayisinde, temizleme ve beyazlatmada, inşaat ve çimento sanayisinde, yanmayı önleyici/geciktirici olarak, nükleer uygulamalarda, enerjide, makine ve metalürjide, sağlıkta ve tarımda kullanımı anlatılarak borun önemi vurgulanmıştır. Daha sonra geniş kullanım alanına sahip borun, özellikle yapı malzemesi alanında kullanımı irdelenmiş, kategorilere ayrılmış ve kullanıldığı malzemeye kattığı pozitif özelliklere vurgu yapılmıştır. Üretiminde bor ve türevleri kullanılan yapı malzemeleri, çalışmanın üçüncü bölümünde; çimento sanayisi, zemin ve duvar kaplama malzemeleri, ahşap ve ahşap kompozit malzemeler ve metal sanayisi olarak kategorilendirilmiştir. Her bir kategori içerisinde, literatürde yapılmış olan deneysel çalışmalar irdelenerek deney sonuçlarından faydalanılmış ve malzemenin bor katkısı ile kazandığı inovatif özelliklere vurgu yapılmıştır. Bu kapsamda incelenen çalışmalardan, çimento bünyesine katılan bor türevleri olan kolemanit ve borojips sayesinde çimentonun pişme sıcaklığında düşme, mukavemetinde artma, üretim maliyetinde düşme, hidratasyon ısısında azalma, yüksek nötron tutma özelliği ile radyasyona karşı koruma, çevre kirliliğinde düşme ve hammaddede tasarruf sağladığı ve ürünün kalitesini arttırdığı görülmüştür. Zemin ve duvar kaplama malzemelerinde katkı maddesi olarak kullanılan bor türevlerinden borik asit, bor oksit ve boraks hammaddeleri sayesinde, genellikle seramik ve porselen karo üzerinde yapılmış olan deneysel çalışmalar ile borun malzemeye kattığı inovatif özellikler belirlenmiştir. Bor katkı oranına bağlı olarak parlak yüzey oluşumu, dokulu yüzey oluşumu, mat yüzey oluşumu, sinterlemeyi kolaylaştırma, pişme sıcaklığını düşürme, malzemenin mukavemetini arttırma, efektli ve lüsterli bir görünüm kazandırma, çevresel etkisini düşürerek daha çevreyle ilgili hale getirme şeklinde sıralanmıştır. Ahşap ve ahşap kompozit malzemelerde yapılmış olan araştırmalara göre borun genellikle ahşap malzemeyi koruma amaçlı kullanıldığı anlaşılmıştır. Borlu bileşikler ile muamele edilen ahşap ve ahşap kompozit malzemelerin, kullanım ömründe, yüzey sertliğinde, yangına karşı dayanımı, çürüklük dayanımı gibi bazı özelliklerinde önemli derecede iyileştirme elde edildiği görülmüştür. Son olarak metal sanayisi kategorisinde incelenen çalışmalar, son yıllarda uygulanmaya başlanan, borun metal malzeme yüzeyine borlama yöntemi ile uygulanmasının, ürünün kullanım ömründe artış, radyasyon tutma özelliğinde artış, yüzey sertliği ve korozyon direncinde artış, metal ergime sıcaklığında düşüş gibi pozitif özellikler kattığı görülmüştür. Literatür tarama, derleme ve yorumlama tekniğiyle hazırlanan bu çalışma ile borun, yapı malzemesi alanına kazandırdığı yenilikler ve inovatif özelliklerinden elde edilen verilere dayalı olarak yapıda kullanılan malzemelerde bor kullanımının olası araştırma alanları belirlenerek öneriler sunulmuştur.

Use of boron in the world is increasing day by day because of the acquiring advantages by using boron minerals in the production phase of materials. For this reason, this study is aimed to evaluate the use areas in the context of building materials. In the flow of this study, firstly ‘boron’ have been introduced, informations have been given about history of boron, boron minerals and fields which use boron minerals have been presented. By using boron in glass industry, in ceramic industry, in cleaning and whitening, in construction and cement industry, as well as preventing and retarding, in nuclear applications, energy fields, machine and metallurgical industry, health fields and in agriculture have been given with the importance of boron. Then, with a wide range of applications, features and the use of structure is examined in the field of material, divided into categories which creates the building materials. And the positive features are emphasized, which boron adds to the materials used. Boron is a multipurpose element. It is a crucial nutrient for plants, an important component in the nuclear industry and the main ingredient of a bizarre fluid called oobleck. Perched next to carbon on the Periodic Table of Elements, boron is a metalloid, a substance with both metallic and nonmetallic properties. Boron compounds have been known for thousands of years, but the element was not isolated until 1808 by Sir Humphry Davy, Joseph-Louis Gay-Lussac (1778-1850) and Louis Jaques Thenard (1777-1857). This was accomplished through the reaction of boric acid (H3BO3) with potassium. However, boron did not become of interest until the twentieth century when it was found that it formed many unusual and complex compounds. It has been during the last forty years that the right physical and chemical properties have been determined. High purity boron produced by electrolysis and vapor deposition methods have made such determinations possible. Today, boron minerals and compounds are used to produce quite a different materials and products in various industrial fields. Very few countries have boron reserves in the world. Among these, Turkey has the 72% of boron minerals of total world reserves and it is in the first rank with this value. With regard to its trading capacity and the existence in Turkey, some important boron minerals are Borax, Kernit, Ulexit, Colemanite, Pandermite and Hydroboraxide. Among these minerals, Colemanite mineral are only present in Turkey and the USA. Most of the Colemanite reserve is located in Turkey. Economically important sources of boron are the minerals colemanite, rasorite (kernite), ulexite and tincal. Together these constitute 90% of mined boron-containing ore. The largest global borax deposits known, many still untapped, are in Central and Western Turkey, including the provinces of Eskişehir, Kütahya and Balıkesir. Global proven boron mineral mining reserves exceed one billion metric tonnes, against a yearly production of about four million tonnes. In the third part of the study, boron and its derivatives which are used in the production of building materials are categorized as; cement industry, floor and wall coverings, wood and wood composites and metal industries. In each category, the results of the experimental studies in the literature have benefited and the importance is taken with emphasising the materials’ innovative features won by the boron additive. Examined studies about the cement industry in this context revealed that adding colemanite or borojips, which are the derivatives of boron found in nature, in the cement structure; decreases cement firing temperature, increases strength, decreases production costs, decreases hydration heat, gives protection against radiation with its high neutron retention properties, saves the raw materials, decreases environmental pollution and imporves the quality of the product. Some of the raw materials needed for cement production abundantly exist in colemanite. Besides, colemanite does not contain any alkali which does not wanted in cement. Colemanite mineral is just a raw material of cement because it mainly contains CaO, SiO2 and B2O3. Boron modified active belite (BAB) cement has been developed by using these main characteristics of colemanite mineral. Also some researchers in the world determined that there have been improvements in the properties of the cement which are produced by using pure boric oxide. In that aspect, those types of studies have been started in our country and it has been determined that colemanite is the most suitable boron mineral in the production of cement. In the category of floor and wall covering materials, experimental studies are mostly conducted on ceramic and porcelain tiles. These studies revealed that boron derivatives which are used as additive minerals are boric acid, borax and boric oxide through raw materials. Innovative features won by adding these boron derivatives are listed as, shiny surface formation, textured surface formation, matte surface formation depending on boron contribution rate, facilitating sintering, reduce the firing temperature, increasing the strength of the material, effected and lustered view, making the material more ecological reducing the environmental impact. Borates are used to initiate glass formation and reduce glass viscosity, helping to form a smooth surface; and to reduce thermal expansion; thus facilitating a good fit between the glaze and the clay. Borates also increase the refractive index, or lustre, of glazes and can enhance their resistance to chemicals. According to experimental studies made in wood and wood composite materials field, Since boric acid and sodium borates are water soluble compounds which are absorbed by the wood surface and then penetrate by diffusion, they can be both used as wood preservatives. Moreover, these inorganic boron compounds are good fire retardants. Boric acid alone or in mixtures with sodium borates, is particularly effective in reducing the flammability of cellulose materials. Borax and Boric acid are therefore used as fire retardants in wood products and cellulose insulation. Lastly, examined studies in the field of metallurgy revealed that, boron in general, used in metallurgy for reducing melting temperature, increasing fluidity, increasing strength of the steel and reduce the corrosion of the refractory material in the furnace. In steel treatments: Boron, as a non-metallic solid element, can penetrate and form an alloy with steel under high temperatures. It forms a molecular bond with the metal. Unlike chrome, boron does not add a layer to the original surface. Boron treatment does the opposite. It removes carbon and other impurities from the steel, leaving a pure iron boride layer with boron. Also, some experimental researches showed that boron significantly increases metals’ radiation retention properties. This study, which is prepared by the method of literature analyse and commentate, states the building materials’ innovative features gain by the use of boron compounds based on data obtained from experimental studies. And pointing out the area which is open to investigate about the use of boron minerals in the field of construction materials as adobe and mud bricks.
The Analysis Of Researches Which Studies Derivatives Of Boron Used In Building Materials
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: Bor; borun kullanım alanları; yapı malzemesi; kolemanit; boraks; üleksit.; Boron; use of boron; building material; colemanite; ulexit; borax.